Protein-energy wasting in maintenance hemodialysis patients – etiology and diagnosis - Rađen, Slavica Dragić; Ristić-Medić, Danijela; Terzić, Brankica; Đurović, Branka; Mijušković, Mirjana (Vojnosanitetski pregled, 2020)
Introduction
Keywords: renal insufficiency, chronic; renal dialysis; malnutrition; nutritional assessment; nutritional status; metabolism; muscular atrophy; risk assessment.